Fertility and Mortality Data for Germany. Recent Progress and Future Challenges - Michaela Kreyenfeld; Rembrandt Scholz (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
In recent years, considerable progress has been made in improving the data infrastructure for fertility and morality researchers in Germany. Several large scale data sets have been made available through the research data centers: the micro-censuses of the 1970s and 1980s, the censuses of the GDR and FRG, the micro-census panel, data from the pension registers, individual level data from the vital statistics, and the central foreigner registers have become available for scientific usage. Vital statistics have been reformed, and the micro-census now includes information on number of children ever born. Despite these improvements, there are still some "weak spots" in Germany's data infrastructure. Germany is lacking official counts of reconstituted families. We know little about the mortality risks of immigrants. In addition, the data infrastructure for studying the socio-economic differences in mortality risks could be improved, thus enabling Germany to catch up with international developments in this area. This paper concludes by making some suggestions for improving the data available.
Keywords: 330; Fertility; Mortality; Demographic Data